1988
DOI: 10.5935/0305-7518.19880017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chemotherapy on antibody levels in lepromatous patients

Abstract: We compare whole cell ELISA antigens (Mycobacterium leprae) and two specific antigens: PG-I, phenolic glycolipid I of M. leprae and M-BGG, a synthetic antigen representing the terminal sugar ofPG-1 for their effectiveness in detecting anti body during chemotherapy. By the end of the 1 st year of treatment, antibody levels to M-BGG had declined by 42% of the initial EL ISA values, by the end of the 2nd year by 61 % and at the end of 3 years by 68%. Declines of similar magnitude were seen with the other antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…However, since these subjects were from an endemic area, we cannot exclude the possibility that they had been infected with M. leprae. Higher seropositivity rates in control subjects from endemic areas compared to those from nonendemic areas have been reported before in studies using the 36 kDa antigen (Klatser et al, 1985) or the phenolic glycolipid antigen of M. leprae (Douglas et al, 1987). The results of this pilot study showed a positive correlation (Pearson correlation test, P < 0.01)…”
Section: Treatmentsupporting
confidence: 73%
“…However, since these subjects were from an endemic area, we cannot exclude the possibility that they had been infected with M. leprae. Higher seropositivity rates in control subjects from endemic areas compared to those from nonendemic areas have been reported before in studies using the 36 kDa antigen (Klatser et al, 1985) or the phenolic glycolipid antigen of M. leprae (Douglas et al, 1987). The results of this pilot study showed a positive correlation (Pearson correlation test, P < 0.01)…”
Section: Treatmentsupporting
confidence: 73%
“…2 Serological tests based on specific M. leprae antigens do not detect all clinical cases because most of the patients at the paucibacillary (PB) stage of infection do not develop significant levels of antibody response. 3,4 This group potentially consists of patients with diverse clinical, bacteriological, and histopathological features. Frequently, M. leprae cannot be detected in the tissues of early lesions, histopathology can be non-specific, clinical findings are inconclusive, and patient histories can be unreliable, making diagnosis of early stage leprosy very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…It has been repeatedly shown that macrophages in MB leprosy patients are not able to clear M. leprae efficiently from lesions because dead organisms and their fragments continue to persist even after the end of treatment (21). Furthermore, in lepromatous patients under therapy, the duration of treatment seems to be a very important factor for the development of anti-PGL-1 levels, since patients treated for as long as 18 months had positive anti-PGL-1 levels, whereas patients treated for a long time (5 years or more) had normal antibody levels (11). A serologic test for the diagnosis of subclinical infection and for therapeutic follow-up has been applied, despite the high specificity and controversies surrounding the correlation of high levels of anti-PGL-1 antibodies with active, previous or future disease (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Serology could provide a method to monitor leprosy patients under treatment since the levels of anti-PGL-1 antibodies decrease during the administration of specific therapy (1). A serologic test for the diagnosis of subclinical infection and therapeutic follow-up has been applied, despite the high specificity and controversies surrounding the correlation of high levels of anti-PGL-1 antibodies with active, previous or future disease (11,12).…”
mentioning
confidence: 99%